Fernanda Bustamante Escalona y Lorena Amaro Castro (eds.), "Carto(corpo)grafías. Nuevo reparto de las voces en la narrativa de autoras latinoamericanas del siglo XXI", Madrid/Frankfurt, Iberoamericana/Vervuert, 2024, pp. 412 - Luna Delmonte (Confluenze)
The review considers the book Carto(corpo)grafías, edited by Fernanda Bustamante Escalona and Lorena Amaro Castro, which collects a set of studies related to contemporary Latin American women's narrative.